Viscozyme L hydrolysis and Lactobacillus fermentation increase the phenolic compound content and antioxidant properties of aqueous solutions of quinoa pretreated by steaming with α‐amylase. Issue 5 (12th April 2021) - Zhang, Jigang; Li, Maoye; Cheng, Jianghua; Zhang, Xinhong; Li, Kexin; Li, Bin; Wang, Chuyan; Liu, Xinmin
Abstract : Abstract: In this work, red quinoa was successively subjected to α‐amylase steaming, complex enzyme Viscozyme (R) L hydrolysis, and lactic acid bacteria (LAB) fermentation. The total phenolic compound content (TPC), flavonoid content (TFC), and antioxidant capacities of the solvent‐extractable (free) and bound fractions and the individual phenolic compounds released were determined. Compared to steaming with α‐amylase, enzymatic hydrolysis and fermentation of quinoa resulted in approximately 82.6, 26.9, 36.3, and 45.2% increases in the TPC (the sum of free and bound fractions), TFC, DPPH, and ORAC values, respectively. HPLC‐QqQ‐MS/MS analysis showed that enzymolysis and fermentation increased the content of protocatechuic acid, catechin, procyanidin B2, and quercetin by 126.3, 101.9, 524, and 296.3%, respectively. Moreover, a major proportion of individual phenolic compounds existed as bound form. The results indicated that complex enzymatic hydrolysis and LAB fermentation were practical and useful to release promising polyphenols. This research provides a basis for the processing of quinoa beverages rich in phenolic compounds. Practical Application: In this work, liquefying with α‐amylase, hydrolyzing with cellulolytic enzyme mixture, and fermenting with Lactic acid bacteria (LAB), successively, were exploited to process quinoa. This is an innovative method of quinoa processing to produce beverage products. Complex enzymatic hydrolysis and fermentation with LAB can significantly enhance phenolic compound, especially protocatechuic acid, catechin, procyanidin B2, and quercetin. In additional, LAB fermentation is very beneficial to improve the antioxidant activity of quinoa. We also found that a major proportion of phenolic compounds existed as bound forms in quinoa.